Changes in hematological parameters of athletes after receiving daily dose of a mixture of 12 amino acids for one month during the middle- and long-distance running training - Ohtani, M.; Maruyama, K.; Suzuki, S.; Sugita, M.; Kobayashi, K. (Bioscience, Biotechnology, and Biochemistry, 2001)
Previous studies have shown that a mixture of amino acids, consisting of 9 essential amino acids and 3 non-essential amino acids was effective in facilitating muscle recovery from athletic activities. In this study, the objective was to determine whether this amino acid mixture improved the physical condition and associated blood parameters of athletes in training when administered for a prolonged period. Thirteen college middle- and long-distance runners were placed in a 6-month experiment and received the amino acid mixture at the dose of 2.2 g/day for one month, 4.4 g/day for one month, and 6.6 g/day for one month with washout periods between test periods. The physical condition was scored and blood samples were collected before and after each test period. When the subjects received 2.2 g of the amino acid mixture three times a day, the physical condition was significantly improved along with increases in red blood cell count, hemoglobin, hematocrit, serum albumin, and fasting glucose, and a decrease in creatine phophokinase (p<0.05), suggesting increased hematopoiesis and glycogenesis, and rapid alleviation of muscle inflammation by the amino acid mixture.